Assessing the impact of sourcing on the performance of ghana water company - MAMPHEY FRED (KNUST, 2024)
A thesis submitted to department of logistics and supply chain management- institute of distance learning in partial fulfillment of the requirement for the award of the degree of master of science (logistics and supply chain management)